The adaptive science communication model in the middle of VUCA era in Indonesia: Study of startup Kok Bisa - Syora Alya Eka Putri; Ricardi S Adnan (Informasi, 2022)
This article analyzes the adaptive science communication model in the VUCA era. Previously, the model of science communication developed by scientific institutions and journalists in Indonesia tended to be challenging to understand by the public. Finally, in the development of technology, the model of science communication developed marked by the emergence of various creators who utilize social media. Nevertheless, due to dynamic conditions, the development of science communication models has not been fully adaptive. In previous studies, these conditions due to dynamic challenges due to the lack of public confidence in science and community participation to curate science tend to be slow in the rapid dissemination of information. This study uses a qualitative approach with case studies of digital data analysis. This study shows that the science communication model can develop more adaptively during disruptive conditions with innovations in social media from the form of presentation and inviting cooperation with other parties, as well as to conduct transformative strategies by building organizational resilience, developing valid information, restructuring, and conducting experiments following organizational capabilities.